Defining national net zero goals is critical for food and land use policy - Bishop, George; Duffy, Colm; Prudhomme, Rémi; Cowie, Annette; O’Donoghue, Cathal; Cain, Michelle; Lanigan, Gary J.; Styles, David (Springer, 2024)
The identification of agriculture and land use configurations that achieve net zero (NZ) greenhouse gas emissions is critical to inform appropriate land use and food policy, yet national NZ targets lack consistent definitions. Here, 3000 randomised scenarios projecting future agricultural production and compatible land use combinations in Ireland were screened using ten NZ definitions. When aggregating carbon dioxide, methane, and nitrous oxide emissions using various methods, 1–85% of scenarios met NZ criteria. Despite considerable variation, common actions emerged across definitions, including high rates of afforestation, organic soil re-wetting, and cattle destocking. Ambitious technical abatement of agricultural emissions moderated, but could not substitute, these actions. With abatement, 95th percentile milk output varied from 11–91% of 2021 output, but was associated with reductions of up to 98% in suckler-beef production, and a 47–387% increase in forest cover. Achieving NZ will thus require transformation of Ireland’s land sector. Lagging land use change effects require urgent action, but sustaining a just transition will require visioning of future NZ land use combinations supporting a sustainable and resilient food system, alongside an expanding circular bioeconomy. We provide new insight into the sensitivity of such visioning to NZ definitions, pointing to an urgent need for international consensus on the accounting of methane emissions in NZ targets.